Iowa RBA, June 3-6, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for June 3-6, 1996. Highlights of the update include sightings of Western Grebe, a pair of Red-breasted Nuthatches, a male Lazuli Bunting, Mississippi Kites and three Peregrine Falcon chicks. Epson - sheet feed/flatbed